2020
DOI: 10.1093/rheumatology/keaa757
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sjögren syndrome: features of an international cohort and application of the 2016 ACR/EULAR classification criteria

Abstract: Objective Sjögren syndrome in children is a poorly understood autoimmune disease. We aimed to describe the clinical and diagnostic features of children diagnosed with Sjögren syndrome and explore how the 2016 ACR/EULAR classification criteria apply to this population. Methods An international workgroup retrospectively collected cases of Sjögren syndrome diagnosed under 18 years of age from 23 centres across eight nations. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 26 publications
5
48
0
2
Order By: Relevance
“…There is no gold standard diagnostic tool for SS with childhood onset and therefore diagnosis is based on expert clinical opinion, which is dependent on findings from the clinical history and examination, functional exocrine gland tests, as well as serological and histological evidence [ 8 ]. Although historically the diagnostic label of ‘primary SS’ has been used for children [ 9 ], recent reports have highlighted the large spectrum of clinical symptoms children present with, which are difficult to map against the classification criteria for adults with primary SS [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is no gold standard diagnostic tool for SS with childhood onset and therefore diagnosis is based on expert clinical opinion, which is dependent on findings from the clinical history and examination, functional exocrine gland tests, as well as serological and histological evidence [ 8 ]. Although historically the diagnostic label of ‘primary SS’ has been used for children [ 9 ], recent reports have highlighted the large spectrum of clinical symptoms children present with, which are difficult to map against the classification criteria for adults with primary SS [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our cohort, patient reported recurrent parotid gland swelling was present in 91% of the paediatric patients, compared to 49% of adult patients. In the scarce literature available on paediatric onset pSS, recurrent parotid gland swelling is seen as an important feature, with a prevalence ranging from 50% to 75% (5,8,10,23). A possible explanation for the high prevalence of recurrent parotid swelling in our cohort might be that it was scored as subjective symptom (reported by the patients), while other studies only scored parotid gland swelling when parotid enlargement was observed by a physician.…”
Section: Discussionmentioning
confidence: 78%
“…Paediatric patients present more often with non-specific extra-glandular manifestations like fever and arthralgias (8). Furthermore, paediatric patients present less often with sicca complaints (5), which is one of the patient-reported entry criteria for the ACR/EULAR classification, and more often with recurrent parotid gland swelling (9,10). The latter is currently only included in the ACR/EULAR criteria as an entry criterium embedded in the glandular domain of the EULAR SS disease activity index (ESSDAI), when parotid, submandibular or lacrimal gland swelling is assessed by clinical examination (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…There are currently no universally accepted classification criteria for sSS and some experts argue that making a distinction between pSS and sSS is not adequate anymore, as both phenotypes represent the same disease [ 4 ]. Moreover, the classification criteria validated in adults have minimal utility in SS with childhood-onset (defined as disease onset before the age of 18 years), as the disease presentation in children and young people, although rare, is different [ 5 ]. This, in addition to the lack of validated classification criteria for childhood-onset SS, further limits the research opportunities for younger people affected by this disease [ 6 ].…”
Section: Introductionmentioning
confidence: 99%